Antimicrobial Activities of Alginate and Chitosan Oligosaccharides Against Staphylococcus aureus and Group B Streptococcus - Asadpoor, Mostafa; Ithakisiou, Georgia-Nefeli; van Putten, Jos P. M.; Pieters, Roland J.; Folkerts, Gert; Braber, Saskia (Frontiers in Microbiology, 2021)
The bacterial pathogens Streptococcus agalactiae (GBS) and Staphylococcus aureus (S. aureus) cause serious infections in humans and animals. The emergence of antibiotic-resistant isolates and bacterial biofilm formation entails the urge of novel treatment strategies. Recently, there is a profound scientific interest in the capabilities of non-digestible oligosaccharides as antimicrobial and anti-biofilm agents as well as adjuvants in antibiotic combination therapies. In this study, we investigated the potential of alginate oligosaccharides (AOS) and chitosan oligosaccharides (COS) as alternative for, or in combination with antibiotic treatment. AOS (1 - 16 %) revealed antimicrobial activity against GBS V by determining the minimum inhibitory concentration. Both AOS (8 and 16 %) and COS (2 - 16 %) were able to prevent biofilm formation by S. aureus wood 46. A checkerboard biofilm formation assay demonstrated a synergistic effect of COS and clindamycin on the S. aureus biofilm formation, while AOS (2 and 4%) were found to sensitize GBS V to trimethoprim. In conclusion, AOS and COS affect the growth of GBS V and S. aureus wood 46 and can function as anti-biofilm agents. The promising effects of AOS and COS in combination with different antibiotics may offer new opportunities to combat antimicrobial resistance.